Collaborative research for personal growth: illustrative stories of the transformative impacts of multidisciplinary SoTL - Nelson, Jody; McKendrick-Calder, Lisa; Carlson, Susan; Shamchuk, Lisa (My University, 2025)
Scholarship of Teaching and Learning (SoTL) inquiry is a type of research that educators can undertake for any or all of the four main categories of research intention identified by Stubb et al. (2014): research as a job, a mechanism to gain qualification, a personal journey, and a way to make a difference. SoTL, historically, was conceptualized with less focus upon the traditional goal of scholarly output to inform others, and instead is described as “practices that engage teachers in looking closely and critically at student learning in order to improve their own courses and programs” (Hutchings et al., 2011, p. xix). SoTL scholars commonly investigate areas of curiosity within their personal context. They seek to uncover insights and generate knowledge to inform their pedagogical practices. Thus, SoTL aligns well with Stubb’s notions of research as a personal journey and a way to make a difference in student learning. When SoTL is undertaken collaboratively across diverse disciplines, it can promote a deeper understanding of effective teaching and learning strategies, and can have a broader impact. It can also cultivate curiosity by aiding researchers to uncover and (re)consider assumptions, explore new research methodologies, and adapt evidence-based practices in their teaching. The reflective process involved can enhance professional identity, build cross-disciplinary connections, and support continuous learning. Additionally, collaboration can foster the development of shared pedagogical knowledge, leading to more innovative and inclusive teaching strategies that benefit students and educators alike. This panel presentation will highlight aspects of each presenters’ personal SoTL journey, sharing their reflections and selected SoTL findings. They will emphasize how multidisciplinary SoTL has contributed to their professional growth while enhancing their personal teaching practices. Their stories will support the potential of utilizing SoTL on a personal journey towards enhanced teaching and learning potential.
Presented on June 11, 2025, at the 2025 STHLE/SAPES Annual Conference in Saskatoon, Saskatchewan.
Keywords: SoTL; teaching practices; disciplinary collaboration